The effect of diethyl ether on interfacial tension and oil swelling in crude oil-brine system - Amir Mohammadi; Mohammad Chahardowli; Mohammad Simjoo (Journal of Petroleum Exploration and Production Technology)
Abstract Solvent injection, a proven method in enhanced oil recovery (EOR), has shown substantial enhancements in oil recovery compared to conventional waterflooding methods. Interfacial tension (IFT) is a critical factor that determines the amount of residual oil in a reservoir and the distribution of fluids within it. This highlights the importance of accurately understanding the interactions at the oil-brine interface. This study marks the first investigation into the effects of Diethyl Ether (DEE) on both the IFT within an oil-brine system and the oil swelling under different salinity and temperature conditions, employing the pendant drop method. The experimental findings demonstrate that the utilization of DEE significantly diminishes the IFT between oil and brine. As temperature and salinity levels rise, the IFT of the oil-brine-DEE system decreases. Nonetheless, this investigation underscores the importance of salinity levels in achieving the most substantial reduction in IFT. The optimal performance of DEE occurs in the seawater (SW) sample at 70 °C, resulting in the lowest IFT at approximately 2 mN/m ( $$\:≈\:$$ 90% reduction) compared to the initial value. Furthermore, the greatest oil swelling was observed in SW compared to all other samples. This remarkable performance is attributed to the synergistic effects of DEE and ions present in the aqueous phase. Additionally, the migration of polar components such as asphaltene molecules to the interface of the oil-brine system should be considered for achieving the highest reduction in IFT. The findings of this study have the potential to advance the understanding of the underlying mechanisms involved in water-soluble solvent EOR technologies.